Digital storyline and QR Code implementation to enhance the tourism appeal of the Kecak Dance - Putu Tika Virginiya; I Putu Bakti Utama; Cinta Rani Ananta; Ni Kadek Dwi Dharmayanti; Ni Putu Wiwik Andika; Ari Karunia Dewi; Muhammad Asrul (University of Merdeka Malang, 2026)
This community service activity aims to increase the appeal of the Kecak Dance performance at Pura Luhur Uluwatu by introducing an innovative digital storyline on the website and utilizing QR codes. This activity was carried out in collaboration with Sekaa Karang Boma as the manager and administrator of the Kecak Dance performance at Pura Luhur Uluwatu as a partner. The implementation method is described through a qualitative descriptive approach that includes eight stages of activities, namely socialization and identification of partner needs, website design and draft presentation, website management and digital marketing training, content development and documentation assistance, to evaluation and delivery of the final product. The QR code directs tourists to the website, allowing them to access information and storylines conveniently via their mobile devices. Socialization and content management training were also provided to Sekaa Karang Boma to ensure the sustainability of this digital media. The evaluation results show that this innovation was positively received by managers and tourists, with an average rating of 4.193 (Good). These findings confirm that the implementation of the community service program was able to improve the effectiveness of promotion and management of digital-based services and contribute to the sustainable strengthening of partner capacity.